Ensuring Consistent Global Branding : An Audit of International Hotel Franchise Networks - Lawalata, Caroline (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This research investigates the brand evaluation process in international hotel franchise systems, emphasizing the consistency of global brand standards across various sites. As globalization in the hospitality sector grows, it is crucial for hotel franchisors to uphold a consistent brand identity, service quality, and customer experience to sustain brand loyalty and competitiveness. The study examines the methods franchisors employ to guarantee that franchisees follow international brand standards and the effects of these standards on customer satisfaction, brand value, and operational effectiveness. This study offers valuable insights into the challenges and best practices for managing an international hotel franchise by performing a thorough audit that assesses brand positioning, marketing strategies, customer feedback, and operational consistency. The results indicate that strong communication, ongoing training, and frequent evaluations of brand performance are crucial for sustaining a cohesive global brand identity. Moreover, the document emphasizes the significance of regional customization while retaining essential brand principles. In conclusion, this research enhances the comprehension of how brand audits can be utilized to guarantee the sustainability and prosperity of global hotel franchises.